The handbook of rational and social choice an overview of new foundations and applications - Anand, Paul.; Pattanaik, Prasanta K.; Puppe, Clemens, 1960- (Oxford : Oxford University Press, 2009)
This volume provides an overview of issues arising in work on the foundations of decision theory & social choice. The collection will be of value to researchers in economics with interests in utility or welfare, but also to any social scientist or philosopher interested in theories of rationality or group decision-making.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social choice; Group decision making